Nonsteroidal Anti-Inflammatory Drugs: A survey of practices and concerns of pediatric medical and surgical specialists and a summary of available safety data - Levy Deborah M; Imundo Lisa F (BMC, 2010)
Abstract Objectives To examine the prescribing habits of NSAIDs among pediatric medical and surgical practitioners, and to examine concerns and barriers to their use. Methods A sample of 1289 pediatricians, pediatric rheumatologists, sports medicine physicians, pediatric surgeons and pediatric orthopedic surgeons in the United States and Canada were sent an email link to a 22-question web-based survey. Results 338 surveys (28%) were completed, 84 were undeliverable. Of all respondents, 164 (50%) had never prescribed a selective cyclooxygenase-2 (COX-2) NSAID. The most common reasons for ever prescribing an NSAID were musculoskeletal pain, soft-tissue injury, fever, arthritis, fracture, and headache. Compared to traditional NSAIDs, selective COX-2 NSAIDs were believed to be as safe (42%) or safer (24%); have equal (52%) to greater efficacy (20%) for pain; have equal (59%) to greater efficacy (15%) for inflammation; and have equal (39%) to improved (44%) tolerability. Pediatric rheumatologists reported significantly more frequent abdominal pain (81% vs. 23%), epistaxis (13% vs. 2%), easy bruising (64% vs. 8%), headaches (21% vs. 1%) and fatigue (12% vs. 1%) for traditional NSAIDs than for selective COX-2 NSAIDs. Prescribing habits of NSAIDs have changed since the voluntary withdrawal of rofecoxib and valdecoxib; 3% of pediatric rheumatologists reported giving fewer traditional NSAID prescriptions, and while 57% reported giving fewer selective COX-2 NSAIDs, 26% reported that they no longer prescribed these medications. Conclusions Traditional and selective COX-2 NSAIDs were perceived as safe by pediatric specialists. The data were compared to the published pediatric safety literature.